2015
DOI: 10.1109/jphot.2015.2421441
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of Random Lasing Action From Dye-Doped Liquid Crystals Infilling Two-Dimensional Confinement Single Core Capillary

Abstract: The experimental detail of a random lasing action from dye-doped nematic liquid crystals (LCs) inside single-core capillaries with a core diameter below 50 m was investigated. The resonant characteristics, including the number of emission spikes, the full width at half maximum (FWHM), and the estimated Q-factor, were shown to depend on the core diameter of a capillary. In contrast with a capillary with a larger core diameter and having various emission spikes, only three emission spikes were excited from a cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…λ p and Δλ are sharp peak wavelength and FWHM, respectively. The Q factor of NaYF 4 :Yb,Er microcavity is about 2700, which is comparable with other random laser systems [ 43 , 46 , 47 ]. As a result, it is verified that NaYF 4 :Yb,Er NCs film supports ultrahigh Q coherent random laser microcavity with low threshold.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…λ p and Δλ are sharp peak wavelength and FWHM, respectively. The Q factor of NaYF 4 :Yb,Er microcavity is about 2700, which is comparable with other random laser systems [ 43 , 46 , 47 ]. As a result, it is verified that NaYF 4 :Yb,Er NCs film supports ultrahigh Q coherent random laser microcavity with low threshold.…”
Section: Resultssupporting
confidence: 70%
“…It is observed that there are plenty of NaYF 4 :Yb,Er NCs, which can satisfy the sufficient scattering between NCs and NCs to realize random lasing. Moreover, sharp peaks with FWHM less than 0.2 nm emerge from the emission spectrum when the excitation power larger than that of the threshold value, as shown in right inset of Figure 4 c. The FWHM of lasing peak is less than that in other reports [ 43 , 44 ]. The Q factor of the NaYF 4 :Yb,Er microcavity can be approximately defined as Q = λ p /Δλ [ 45 ].…”
Section: Resultsmentioning
confidence: 72%
“…When some of the rays return to their starting positions under constructive interference, a closed-loop path (dashed line) will be formed and enable coherent light. If the amplification along such a loop patch exceeds the loss, laser emission will occur [11,24,25]. The random lasing obtained here was unpolarized.…”
Section: Methodsmentioning
confidence: 74%
“…Miniaturizing liquid dye lasers into a microfluidic device has many potential advantages such as compactness, easy maintenance, safe laser operation, accurate spatial mode control, and low threshold energy [3][4][5][6][7] with a wide range of applications including chemical and biological sensing [8,9]. Microfluidic fiber lasers have also appeared in optical fiber platform resulting in dye fiber lasers [10][11][12][13][14][15][16][17]. Fiber lasers based on capillary tubes and photonic crystal fibers filled with a dye solution were studied in detail by Vasdekis et al [10].…”
Section: Ocis Codesmentioning
confidence: 99%